CONTEMPORARY VIEWS ON PERIPARTUM CARDIOMYOPATHY — CLINICAL PICTURE, DIAGNOSTICS, COURSE, TREATMENT (PART II) - N. T. Vatutin; G. G. Taradin; S. M. Kornienko; A. A. Taratorina; V. V. Ridzhok (Российский кардиологический журнал, 2015)
The second part of the review of peripartum cardiomyopathy includes contemporary views of a specifics of disease onset. Detailed specifics of the disease onset is provided according to their specificity and diagnostical value. The approaches to diagnostics described beginning from physical examination to instrumental methods. Taking into account of the microparticles role on the disease onset, the importance ov their measurement is highlighted in peripartum cardiomyopathy, especially peripheral vasodilators, diuretics, ACE inhibitors, antiarrhythmic drugs, anticoagulants, pentoxyphilline, bromocryptine, cabergoline. The methods selected of artificial circulation in severe disease course and the data provided on plasmapheresis usage and implantable cardioverter-defibrillator. In general the points of delivery problems discussed.